A pornografia e a proteção à infância: a regulação de plataformas digitais - Rangel, Jackeliny Ferreira (2023)
This is a research that aims to address the regulation of digital platforms in view of the needto safeguard the Fundamental Rights of children, in the digital environment, especially with regard to their exposure to pornography. Using the deductive method and qualitative approach, through bibliographical and documental research, firstly, digital platforms are analyzed, in their general aspects and also regarding the attribution of responsibility for third- party content. Further on, in the chapter on “Pornography and Children”, an overview is made of the Human Rights of children and aspects of pornography, emphasizing the current guise in which it is presented, completely disseminated on digital platforms, configuring a risk of exposure to children, who may have their mental, psychological and social development harmed by the use of pornography. In Chapter 3, the constitutional and infraconstitutional legislationis evaluated and its relevance to the theme of protecting the psychological fragility of childrenwhen exposed to pornography on networks. The research concludes by pointing out regulatory possibilities, in view of the verification of omissions in the national legal system, which undermine the adequate protection of the legal interest, that is, the hypervulnerability of children in the digital environment.